POETICS OF LITERARY-CRITICAL TEXT - Makhmudova Dilafruz Salimjonovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article examines the poetics of a literary-critical text. The conclusions of many scientists are used in the substantive coverage of the topic.